Most Chinese Preschool Teachers Value Guided Play Over Free Play: Latent Profiles and Associated Predictors - Lin, Xunyi; Liao, Yutong; Xue, Manli; Colliver, Yeshe (Frontiers in Psychology, 2021)
Background: Longitudinal research suggests that optimal long-term outcomes are achieved when early childhood education and care (ECEC) balance free with guided play. A prerequisite for this achievement is that ECEC teachers value both equally. Research Findings: This study examines preschool teachers’ play beliefs profile and explores its association with teachers’ backgrounds (e.g., teaching experience, education level) in a sample of 674 Chinese teachers in Fujian, China. Participants completed an adapted form of the Parent Play Belief Scale, the Chinese Teacher Play Beliefs Scale, to report their beliefs regarding young children’s play and early academics. Latent profile analysis revealed 91% of teachers exhibited high Guided Play for Academics Support (GPAS) and low Free Play for Socio-Emotional Skills Support (FPSSS), whereas only 9% were high in both factors. Teachers with a decade or more teaching experience were more likely to belong to the high GPAS and low FPSES profile. Practice and Policy: The findings indicate that the majority of Chinese ECEC teachers value guiding play to academic skills more than they do facilitating free play for socio-emotional skills. Professional development focused on balancing guided with free play may be necessary for the majority of Chinese ECEC teachers to catch up with the zeitgeist of contemporary international research and policy on intentional teaching in play.